This Is What Climate Change Looks Like: McKenzie Wark's Post-Literary Critiques Give Equal Value to Participation. Issue 1 (April 2022) - Giunta, Carrie
Abstract : This essay revisits a debate about literary fiction's ability to depict the consequences of climate change. Philosopher McKenzie Wark's 2017 essay, 'On the Obsolescence of the Bourgeois Novel in the Anthropocene', offers one of many critiques of climate fiction, such as Amitav Ghosh's influential book, The Great Derangement . But while Ghosh sees a shortcoming in contemporary novels in their lack of representation of major climate events, Wark emphasises the importance of collective action, conversation, and connection, beyond the limits of literature. Since Wark's intervention, the global School Strike for Climate in 2019 and 2020 brought more participatory post-literary forms to represent climate change. Jean-Luc Nancy's theory of participation, that there is no mimesis without participation ( methexis ), sees a tense relation between the two rather than an opposition or conflict. I argue that Wark, by not undervaluing participation, disrupts a hierarchy that privileges the imitator at the expense of the imitation. To explore this relation, I consider how the slogan 'there is no Planet B' forms a snapshot of our twenty-first-century mimetic condition, from which no imitative representation will save us. Can Wark expand the vision of another relational kind of femininity in her later writing to support the demand to take part in transformational action against climate catastrophe, beyond mimetic representation carried in the form of the novel?